"Attempts to Change the World Itself": American Political Theory and Rhetorics of Political Significance. Issue 3 (2nd July 2020) - Dorzweiler, Nick
ABSTRACT: Although the subfield of political theory often struggles to be recognized as producing scholarship that meaningfully contributes to the practical improvement of American political life, claims concerning the potentially immense political significance of theory work remain prominent within the subfield itself. The primary aim of this article is to demonstrate that such claims are manifestations of a rhetoric that has circulated in American political theory for much of the twentieth century. The second is to argue that political theorists should seek to modify this rhetoric. This is not only because it is incongruent with the material, institutional, and professional circumstances that largely define and increasingly contain academic political theory today. It is also because its very rootedness within the subfield may also be occluding recognition of other, more credible, and more unabashedly quotidian ways of speaking of the political significance of theory work.